A systematic review of factors influencing attitudes towards and intention to use the long-distance caregiving technologies for older adults. (September 2021) - Wang, J.; Fu, Y.; Lou, V.; Tan, S.Y.; Chui, E.
Highlights: Factors affecting older adults' attitude and intention to use long-distance-care technologies. Importance of balancing functionality and privacy concerns among older adults. Implications for various stakeholders in formulating appropriate strategies. Abstract: Purpose: Long-distance caregiving (LDC) technologies play a significant role in enabling distant care and facilitating living-alone older adults to keep socially connected. However, there is scarce research exploring the older adults' attitudes towards and intention to use such technologies. This paper is based on a systematic review of existing literature to explore the multifarious factors influencing independent community-living older adults' attitudes towards and intention to use LDC technologies. Methods: Articles published in English between 2006 and 2020 were reviewed by searching electronic databases of PubMed, ProQuest, EBSCOhost. The inclusion criteria were limited to quantitative, qualitative, or mixed-methods studies that involved: 1) distant caregiving; 2) older adults aged 60 years or above, who were living alone or with only their spouse in the community (even though the samples might also involve other non-older adults); 3) technologies including ICT-based devices, systems, or programs enabling data transmission were used; 4), intention to use or behavioral usage in regard to the technologies were reported or discussed. Results: In total, 41 out of 8674 articles were included. Both determinants and moderators of affecting the use of the ICT-based LDC technologies were identified with theoretical guidance. To summarize, there are personal factors involved, such as personality, concerns regarding security and privacy, health conditions, requisite knowledge, financial conditions, and influence from significant others, encompassing formal and informal caregivers; and factors related to the devices, in terms of their user-friendliness and functionality. Conclusion: This review highlights the importance of striking a good balance between functionality and privacy concerns, besides considering the direct and indirect cost to users. LDC technology education should be promoted at the societal level to facilitate older adults' better understanding of the device utilities by enhancing their technological literacy. Implications for various stakeholders to cope with the challenges of an aging population are also discussed.